Effect of Mnemonic Method on the Ability to Recall Social Studies in MTs NU Ungaran - Sekarwati, Putri; Kustiono, Kustiono (Jurnal Penelitian Pendidikan, 2020)
It was observed that some students had difficulty in remembering learning material because the delivery of material was less interesting and enjoyable. The purpose of the study was to find out the difference in the ability to remember students using the mnemonic method and students with the lecture method in social studies subjects. Research design with quasi experiment. The results showed the ability to remember students on pre-test with an average of 52 and increased at the post test by 79.8. for the control class in the pre test has a value of 52.4 increased to 76.3 in the post test. The conclusion of the research is that there is a difference in the improvement of the ability to remember between students who use the mnemonic method and students who learn by the lecture method, with t arithmetic (4,120) t table (2,023), so that the use of the mnemonic method is more effective in improving the ability to remember compared to the lecture method on the eyes social studies lessons.